СОЦИОЛИНГВИСТИЧЕСКАЯ ИНФОРМАЦИЯ В СЛОВАРЯХ ГОРОДСКОЙ РЕЧИ (Philological Studies, 2019)
The social approach to the facts of the language is not new in the history of linguistics at the same time it cannot be called to be out-of-date. Nowadays it’s impossible either to set or solve many of linguistic issues without interpreting and studying various social factors. Studying urban speech (slang) focuses not only on studying sublanguage systems but also on language functioning. That said speech is treated as a separate entity with its own formal features and semantics. Communication is essentially determined by social interaction. Studying oral speech in different Russian towns (such as Saratov, Yekaterinburg, Chelyiabinsk etc.) contributes to theoretical background for urban dialects dictionary with the emphasis being made on the lexicographic technique which is widely used to describe oral speech and its peculiarities. Lexicography, being a linguistics tool, has a great potential, for the emphasis on word usage contributes to the appearance of dictionaries representing the interests of their various users. The goal of these dictionaries (for example Jargon dictionary professional lexicon, urban speech as a whole etc) is to demonstrate the way a speech unit functions. The article presents a possible dictionary classification and gives a detailed description of the glossary of Perm localisms being written in Perm State University, In addition to the traditional information a dictionary entry describes the way localisms are formed, the information about age group, social strata and the area typical of such localism. The information contained in a dictionary entry results in a new type of lexicographic dictionary.